Activation of central aα-adrenoceptors mediates salivary gland vasoconstriction - Moreira, Thiago S.; Takakura, Ana C.; Menani, José Vanderlei [UNESP]; Colombari, Eduardo [UNESP] (Elsevier, 2013)
Objective: Peripheral treatment with the cholinergic agonist pilocarpine increases salivary gland blood flow and induces intense salivation that is reduced by the central injection of moxonidine (aα-adrenoceptors/ imidazoline agonist). In the present study, we investigated the effects of the intracerebroventricular (i.c.v.) injection of pilocarpine alone or combined with moxonidine also injected i.c.v. On submandibular/sublingual gland (SSG) vascular resistance. In addition, the effects of these treatments on arterial pressure, heart rate and on mesenteric and hindlimb vascular resistance were also tested. Design: Male Holtzman rats with stainless steel cannula implanted into lateral ventricle and anaesthetized with urethane + α-chloralose were used. Results: Pilocarpine (500 nmol/1 μl) injected i.c.v. Reduced SSG vascular resistance and increased arterial pressure, heart rate and mesenteric vascular resistance. Contrary to pilocarpine alone, the combination of moxonidine (20 nmol/1 μl) and pilocarpine injected i.c.v. Increased SSG vascular resistance, an effect abolished by the pre-treatment with the α2-adrenoceptor antagonist yohimbine (320 nmol/2 μl). The increase in arterial pressure, heart rate and mesenteric resistance was not modified by the combination of moxonidine and pilocarpine i.c.v. Conclusion: These results suggest that the activation of central α2- adrenoceptors may oppose to the effects of central cholinergic receptor activation in the SSG vascular resistance. © 2012 Elsevier Ltd. All rights reserved.
Keywords: α2-Adrenergic receptor; Blood flow and vascular resistance; Moxonidine; Parasympathetic; Pilocarpine; Salivary gland; Rattus